2018
DOI: 10.1016/j.jvs.2018.06.012
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Stroke or Death Is Associated With the Timing of Carotid Artery Stenting for Symptomatic Carotid Stenosis: A Secondary Data Analysis of the German Statutory Quality Assurance Database

Abstract: Background--Subgroup analyses from randomized trials indicate that the time interval between the neurologic index event and carotid artery stenting is associated with periprocedural stroke and death rates in patients with symptomatic carotid stenosis. The aim of this article is to analyze whether this observation holds true under routine conditions in Germany.Methods and Results--Secondary data analysis was done on 4717 elective carotid artery stenting procedures that were performed for symptomatic carotid ste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 29 publications
(59 reference statements)
1
3
0
Order By: Relevance
“…15 Tsantilas et al found a complication rate of 4.65% in the patients treated with CAS within the first week and a 3.9% rate in patients treated between 8 to 180 days. 4 These results are comparable to the rate of minor complications found in our elective CAS group (4.8%), and lower than our emergency CAS group (9%). This higher proportion in our emergency CAS group might be due to the higher rates of tandem occlusions and ipsilateral carotid occlusions, which demonstrated to be an independent risk factor for the composite of primary and secondary outcomes in the multivariate analysis.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…15 Tsantilas et al found a complication rate of 4.65% in the patients treated with CAS within the first week and a 3.9% rate in patients treated between 8 to 180 days. 4 These results are comparable to the rate of minor complications found in our elective CAS group (4.8%), and lower than our emergency CAS group (9%). This higher proportion in our emergency CAS group might be due to the higher rates of tandem occlusions and ipsilateral carotid occlusions, which demonstrated to be an independent risk factor for the composite of primary and secondary outcomes in the multivariate analysis.…”
Section: Discussionsupporting
confidence: 83%
“…Regarding CAS timing, Song et al and Tsantilas et al found that early symptomatic CAS (within two weeks and one week, respectively) had more events (stroke or death) within 30 days post-procedure and during hospitalization than the delayed group (>2 weeks and 8 to 180 days, respectively). 4,5 In contrast, other studies supported early CAS within their 7 or 15 days cut-off, showing no significant differences in stroke or deaths at 30 days. 6,7,17,18 A recent prospective study compared CAS to CEA when performed within the first 48 hours and found similar rates of stroke or any cause of death within 30 days (5.1% vs. 4.9%, respectively).…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations